Pengaruh Defisit Fiskal terhadap Pertumbuhan Ekonomi di Indonesia Periode 1990-2012 - Swasono, Dwinanda Ardhi; Martawardaya, Berly (UI Scholars Hub, 2015)
This research is conducted to investigate the correlation of fiscal deficit to economic growth in Indonesia during 1990-2012. Contribution of this study is the use of cointegration and Error Correction Model, we confirmed mainstream macroeconomic theory where fiscal deficit has positive and significant impact to economic growth. Government is recommended to undertake fiscal deficit within the 3% boundary allowed by State Budget Law.